2022
DOI: 10.3390/horticulturae8020119
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Morpho-Anatomical and Eco-Physiological Responses of Viburnum tinus L. var lucidum as Modulated by Sodium Chloride and Calcium Chloride Salinization

Abstract: Salinity in water and soil is among the major constraints to the cultivation of ornamental crops since it can affect their growth and aesthetic value. A greenhouse experiment was carried out to assess whether the application of two different salts (80 mM NaCl or 53.3 mM CaCl2, with a final ionic concentration of 160 mM) could differently modulate the anatomical and physiological acclimation of an important ornamental species such as Viburnum tinus L. var. lucidum. Eco-physiological analyses (e.g., leaf gas exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
(85 reference statements)
1
3
0
Order By: Relevance
“…In the present study, NaCl treatment caused a significant reduction in stomatal index percentage, stomatal area, and opened stomata, which was accompanied by wrinkling and shrinkage of epidermal walls. These findings agreed with those of Mohamed et al [ 50 ], De Micco et al [ 51 ], and El-Dakak et al [ 52 ], who reported reduced stomatal index percentage and stomatal width in different plant species under salinity stress. Additionally, many factors regulate stomatal mechanics, including ABA, NO, specific ions, and water channels [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, NaCl treatment caused a significant reduction in stomatal index percentage, stomatal area, and opened stomata, which was accompanied by wrinkling and shrinkage of epidermal walls. These findings agreed with those of Mohamed et al [ 50 ], De Micco et al [ 51 ], and El-Dakak et al [ 52 ], who reported reduced stomatal index percentage and stomatal width in different plant species under salinity stress. Additionally, many factors regulate stomatal mechanics, including ABA, NO, specific ions, and water channels [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, several studies have demonstrated the opposite. Mild and moderate CaCl 2 concentrations can lead to more intense phytotoxic effects than NaCl due to the bivalent nature of the former, the increased chloride concentration, and its toxic effects [ 86 , 145 , 146 ]. Moreover, Cl uptake and transport from the roots to the leaves is not as controlled as that of Na, thus drastically affecting plant metabolism and development [ 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cl uptake and transport from the roots to the leaves is not as controlled as that of Na, thus drastically affecting plant metabolism and development [ 147 , 148 ]. Nevertheless, the effect of Na, Cl, and Ca on the morphology, photosynthetic capacity, and ion accumulation might differ between plant species and can be a result of different salinity acclimation strategy [ 145 , 149 , 150 , 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…The improved nutritional status of the CS growing media contributed to the high leaf nutrient concentrations, which results in an optimal growth [45]. The Mg leaf concentrations have been demonstrated to be similar in all CS growing media, indicating good maintenance of photosynthesis performance [46]. In addition, plants did not show changes in chlorophyll content, as chlorophyll degradation should be expected at Mg-limited conditions [47].…”
Section: Discussionmentioning
confidence: 95%